Characteristics and outcome of ambulatory heart failure patients receiving a left ventricular assist device. (7th September 2021) - Baudry, Guillaume; Nesseler, Nicolas; Flecher, Erwan; Vincentelli, André; Goeminne, Céline; Delmas, Clément; Porterie, Jean; Nubret, Karine; Pernot, Mathieu; Kindo, Michel; Hoang Minh, Tam; Rouvière, Philippe; et al.
Abstract: Aims: Despite regularly updated guidelines, there is still a delay in referral of advanced heart failure patients to mechanical circulatory support and transplant centres. We aimed to analyse characteristics and outcome of non‐inotrope‐dependent patients implanted with a left ventricular assist device (LVAD). Methods and results: The ASSIST‐ICD registry collected LVAD data in 19 centres in France between February 2006 and December 2016. We used data of patients in Interagency Registry for Mechanically Assisted Circulatory Support Classes 4–7. The primary endpoint was survival analysis. Predictors of mortality were searched with multivariable analyses. A total of 303 patients (mean age 61.0 ± 9.9 years, male sex 86.8%) were included in the present analysis. Ischaemic cardiomyopathy was the leading heart failure aetiology (64%), and bridge to transplantation was the main implantation strategy (56.1%). The overall likelihood of being alive while on LVAD support or having a transplant at 1, 2, 3, and 5 years was 66%, 61.7%, 58.7%, and 55.1%, respectively. Age [hazard ratio (HR) 1.03, 95% confidence interval (CI) 1.00–1.05; P = 0.02], a concomitant procedure (HR 2.32, 95% CI 1.52–3.53; P < 0.0001), and temporary mechanical right ventricular support during LVAD implantation (HR 2.94, 95% CI 1.49–5.77; P = 0.002) were the only independent variables associated with mortality. Heart failure medications before or after LVAD implantation were not associated with survival. Conclusion: Ambulatory heart failure patients displayed unsatisfactory survival rates after LVAD implantation. A better selection of patients who can benefit from LVAD may help improving outcomes.